Research on Autodocking Control Technology of the Propellant Umbilical Connector of Launch Vehicles - Penghui Wu; Guokun Zheng (International Journal of Aerospace Engineering)
Aimed at the unattended requirements of the heavy launch vehicle filling and launching support system, this paper focuses on the propellant filling and discharge automatically. This paper adopts the parametric variable frequency and amplitude variation equation to simulate the motion of the launch vehicle under wind load conditions. The equivalent spring damping model is used to simulate the real flexible umbilical arm of the rocket. In this paper, the compound active disturbance rejection control and robust integral sign control (CADRCRISC) method is proposed, including feedforward compensation control, linear feedback control, robust control, and extended state observer (ESO) control. This method can adapt to external disturbances and achieve high-precision follow-up control, which is verified through experiments and simulations. The method can adaptively realize fast-following responses and regulate against any disturbance. The research on the automatic docking control technology of the combined connector is of great significance to the unattended launch support system for heavy launch vehicles. Besides, the control method proposed in this paper can be applied in other similar automatic docking applications.